1942
DOI: 10.1084/jem.75.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Cell State as Affecting Susceptibility to a Virus

Abstract: Rabbit skin can be rendered abnormally susceptible to papilloma virus infection by preliminary treatments with a variety of agents. The most effective agents thus far found are 0.3 per cent methylcholanthrene in benzene and a mixture in equal parts of turpentine and acetone, applied four or five times at 2 day intervals. When virus is inoculated into skin altered by these agents, either intradermally or by inunction after scarification, papillomas appear earlier and in greater number than on normal skin, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1943
1943
2008
2008

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…In our study, viral DNA was inoculated by a biobalistic method without skin pretreatment. In the experiments of Hu et al (34), skin was chemically pretreated and scarified prior to DNA inoculation, which increases the susceptibility to CRPV infection (23). The resulting epidermal hyperplasia and wound healing involve the release of the slow-cycling, self-renewing epidermal stem cells from the tight microenvironmental control that ensures the homeostasis of the epidermis (1,61).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, viral DNA was inoculated by a biobalistic method without skin pretreatment. In the experiments of Hu et al (34), skin was chemically pretreated and scarified prior to DNA inoculation, which increases the susceptibility to CRPV infection (23). The resulting epidermal hyperplasia and wound healing involve the release of the slow-cycling, self-renewing epidermal stem cells from the tight microenvironmental control that ensures the homeostasis of the epidermis (1,61).…”
Section: Discussionmentioning
confidence: 99%
“…NZW outbred rabbits were purchased from Covance (Denver, Pa.), and EIII/JC inbred rabbits were bred and maintained in the animal facilities of the Pennsylvania State University College of Medicine. Prior to viral DNA challenge, the backs of the rabbits were shaved and painted with a mixture of turpentine and acetone (50:50 [vol/vol]) four times in total, once every other day, to make the skin hyperplastic (13,25). Viral DNA constructs (10 g per site) were placed onto scarified sites in 50-l volumes.…”
Section: Methodsmentioning
confidence: 99%
“…The question was asked whether simple wounding of the skin prior to infection would be adequate. For many years, investigators have shown that wounding confers an advantage to the virus (Friedewald, WF, 1942). Other studies have led to the hypothesis that wounding increases epidermal cells that are the likely targets of CRPV infection .…”
Section: Introductionmentioning
confidence: 99%